Una prospección a la población de perros existente en las calles de la ciudad de Santiago, Chile - Ibarra, Luis; Espínola, Fabián; Echeverría L., Mario (Avances en Ciencias Veterinarias, 2006)
With the purpose to estimate the size population of dog’s that circulates along the streets of Santiago city, Chile, a random samplin in the urban zone of the city carried out the observation of 864 chosen city block. To obtain the information, a guideline of observation was applied by veterinary professionals and personnnel responsible for programs of control of the environment, in which the caracteristics of the urban each point of sampling, was registered. The results showed that the most important proportion of dogs in Santiago streets, is the free roaming dog with owner with 52,4% (mainly made and adult). These, together with the dogs supervised by owners, they determine that a 69,2% of the dogs that circulate along the streets of the city, had owner, estimating a population of 150, 139 dogs. The dogs without owner, this is stray dogs and neighborhood or community dog, they are reckonoed on 64,794 animals, what determines a total of 214,933 dogs. The presence of these animals in the street generates a series of environmental problems that are of public health corcern.